The Relationship Between Elevated Systemic Immune-Inflammatory Index (SII) and the Severity of Coronary Lesions in Chronic Coronary Syndrome (CCS) Patients Undergoing Coronary Angiography at Haji Adam Malik Hospital Medan - Fatraya, Qien Jovan; Safri , Zainal; Lubis , Anggia Chairuddin (CoinReads Media Prima, 2025)
Introduction: This study examines the correlation between Systemic Immune Inflammation Index (SII) and coronary lesion severity in Chronic Coronary Syndrome (CCS) patients using the SYNTAX score. Inflammatory markers, including neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR), and platelet-lymphocyte ratio (PLR), are associated with atherosclerosis and CAD. Methods: This retrospective observational study analyzed correlation between SII values and coronary lesion severity in CCS patients who underwent coronary angiography. Data were collected between June and August 2024. Patients were categorized based on the SYNTAX score, which evaluates coronary lesion severity. The study used statistical tests including mean tests, multivariate logistic regression, Spearman correlation, and ROC curve analysis to assess SII's sensitivity and specificity in predicting lesion severity. A p-value <0.05 was considered significant. Results: The study subjects were 115 samples with an average age of 59.41 ± 9.45, with 78 male samples (67,8%). It was found that the SII value has a strong correlation with the SYNTAX score, specifically with a mild SYNTAX score of 365.7 (183.45 - 853.91), a moderate SYNTAX score of 695.52 (534.83 - 1838.57), and a severe SYNTAX score of 1026.7 (413.57 - 3813.83; p value <0.001). Conclusion: The study found a significant relationship between SII value and coronary lesion severity, measured by SYNTAX score. Higher SII values were associated with more severe coronary lesions, suggesting SII can serve as an effective predictor of lesion severity in CCS patients.